EFFORTS TO IMPROVE STUDENTS’ MATHEMATICAL PROBLEM SOLVING ABILITIES OF CLASS VII F CIDAUN 1 JUNIOR HIGH SCHOOL TO PLANES MATERIAL THROUGH JIGSAW METHOD - Ening Yuningsih; Asep Ikin Sugandi (IKIP Siliwangi, 2020)
A passive class condition is one of the factors causing low mathematical problem solving ability, where students are less involved in learning. Cooperative learning is an alternative in improvement. The research was conducted in Cidaun 1 Public Middle School, amounting to 30 people precisely in class VII.F in the even semester of the school year 20018/2019. The results showed that the first cycle test obtained an average score of 43.7%, after the implementation of the jigsaw type cooperative learning model, the cycle II test obtained an average score of 63.8 % and the cycle III test obtained an average score average of 72.2%. The number of students who pass the increase on the first cycle of 16.66%, 36.67% for the second cycle and the third cycle of 63.34%.